Untersuchungen zur Reliefentwicklung im nördlichen Rheinhessen - Beck, Nordwin (ERDKUNDE, 1976)
During its uplift in the Pleistocene the limestone plateau of northern Rheinhessen underwent fluvial dissection. Taking place from the outer edge of the plateau, the erosion led to the formation of a rim of piedmont surfaces, deposed in sequences, in front of the escarpment. Glacis and pediments were formed. Cryoturbations, ice wedges on the surface sediment of these base levels, as well as morphometric and situmetric measurements of limestone rubble with rounded edges, have shown that the base levels were created by predominantly fluviatile erosion in a humid, periglaeial climatic zone. The older base level remnants, using the main terrace level of the Wiesbach as a main drainage channel, contain the molar remains of the Elephas meridionalis in the gravel of the superficial strata, and are therefore classified as belonging to the middle Pleistocene. The younger glacis terraces, which were aligned with the middle terrace of the Wiesbach or its tributaries, could be dated as belonging to the Riss glaciation, since the glacis gravel is superimposed by soil of the Eem period, which is in turn covered by a loess profile of the Würm period. In consideration of the morphogenesis the descriptions “Plateau- and glacis-land or “Plateau- und Plattenland are suggested for the northern part of Rheinhessen.